Frobisher's bells: commodities or gifts? - Haines, John Dickinson (The sixteenth century journal, 2016)
In 1576 Martin Frobisher captured an Inuk man off the coast of Baffin Island using several bells. These sounding objects were viewed in two fundamentally different ways. The Inuk considered them to be soul-filled gifts; all things, and especially sounding things, were said by the Inuit to have a guardian spirit. For Frobisher, however, as for most European merchant adventurers from the late 1400s onwards, bells had a specific function within the early capitalist enterprise. They were trinkets that helped get commodities by securing the trust of native peoples. For this reason, Frobisher brought along with him over three hundred bells on his first journey into the Arctic. Not yet considered a commodity in the classic economic sense, bells in the late sixteenth century were called "trinkets," trinkets that were indispensable to making contact with indigenous Americans and to getting at the many commodities the Americas had to offer.